The Dating Again Phenomenon a qualitative study on selected widowed and separated women in Leyte. - Caratao, Sarah Jean L., et al; Colima, Maricris L.; Oja, Maria Ludica B. (Sarah Jean L. Caratao, 2011)
Much of the previous research on dating is focused on the close relationships of younger adults, with little attention given to individuals dating in their later life. In addition, widowhood and separation is a disruptive and inevitable phenomenon for many older people, few studies have explored either adjustment to single life or the prospect of dating and its process in the Philippines. This research is an exploration of the dating again phenomenon as practiced by widowed and separated women in selected areas in Leyte namely Carigara, Leyte, Matalom, Leyte, and Tacloban City. Respondents (n=20) of this study comprised of ten widows and ten separated women were selected at each locality using convenient sampling method. Data was gathered through a survey questionnaire and an in-depth interview of the 20 respondents to determine their dating views, beliefs, preferences and problems encountered while engaging in dating again. Result shows that separated women date goers cite three reasons for dating namely: (a) to have someone whom they could share the same interest, (b) for financial help and (c) to have the lifetime partner. While the widowed women prefer not to date romantically and devote their time into family affairs. Majority of the respondents preferred group dating rather than romantic date with opposite sex although in the case of separated women they are more inclined to date romantically first then degrade to group dating eventually while most of the widow respondents opt to stay single than to remarry again. Problems that hinder these women from dating includes, gossips, reactions of the children and in-laws, having less interest in dating activity due to their age, hesitant to trust and conflict among the family of the guy they are dating with. It is postulated that preconceptions of dating with. It is postulated that preconceptions of dating in their younger years differed to what the widows and separated women have after their initial marriages.